As condições ambientais da microbacia hidrográfica do Lajeado da Represa, município de Marcelino Ramos/RS - Tápia, Brasinicia Tereza (2006)
This work aimed at to study the main current environmental problems of the use of the earth, and their reflexes in the quality of the water, as well as the attitude of the population local front to the environmental degradation that happen in the hydrographical basins of the Lajeado da Represa municipal district of Marcelino Ramos, State do Rio Grande do Sul.For such, the used methodology included, in a first moment, readings that gave support the theoretical revision and field works that served as subsidy to characterize the environmental situation of the basins hydrographical of the Lajeado da Represa. In a second moment, the elaboration and application of a research instrument (questionnaire), with variables regarding the environmental theme to verify the residents' posture in relation to the environmental conditions of the Lajeado da Represa. Later, it was elaborated the thematic letters important support instrument for the environmental evaluation of the area. And, finally it was looked for to characterize the quality of the water and his relationship with the use of the earth applied the slopes of the hydrographical basins. The samples of water were collected in the nascent and in some points of the course of the Lajeado da Represa, mainly in the places where it existed the evidence of garbage deposits and sewer. For the evaluation of the quality of the water the following parameters were considered: color, overcast, STD (solids total dissolved), total hardness, pH, electric conductivity, chloride, fecal and total coliformes. Through the collected information (field observations and physiochemical and bacteriological parameters accomplished) it was possible to describe the environmental conditions of the hydrographical basins of the Lajeado da Represa and to point the attitude of the population local in relation to its preservation and conservation. The results obtained reveal that the hydrographical basins in study presents an intense environmental degradation, due to the human interventions, caused by the pollution of the water, deforestation, assoreament and garbage presence, that commit the balance of the ecosystem and the quality life s of the population.